ASR, Volume 19, n° 1, 2015 - Full Issue - journal system, (African Sociological Review, 2015)
Contents Editorial ..........................................................1 General Issue Ndorobo Notions of Relationship with Other Shelly Ashdown ...............................................2 Strengthening Peace Research and Peace Education in African Universities Kenneth Omeje ................................................16 Research Papers Recreating African Futures through literary imagination. The newest gender, racial, national and African identities as revealed in Mario Lúcio Sousa’s O Novíssimo Testamento Catarina Martins..........................................................................34 Family Structure, Race, Gender and Poverty: the Case of Food Deprivation in South Africa Acheampong Yaw Amoateng and Boitumelo Marilyn Patience Setlalentoa .........................43 Knowledge of Sexually Transmitted Diseases amiong Secondary School Adolescents in Asa Local Government of Kwara State, Nigeria Joseph A. Oluyemi, Mohammed A. Yinusa, Raji Abdullateef,Akoli Sunday and Kadiri Kehinde ...........................63 Les Jeux video en Negroculture: Contribution a une Anthropologie de la solidarite Chezles Jeunes du Cameron Paul Ulrich Otye Elom .............................................................77 Workplace Hazards and Social Positioning Effects on Male Adolescent Labourers in Suburban Sawmills, Lagos State Nigeria Ojo Melvin Agunbiade ..............................................................89